Synthesis of colchifulvin, a colchicine–griseofulvin hybrid. Issue 14 (6th April 2016) - Marset, Azucena; Caprioglio, Diego; Torretta, Simone; Appendino, Giovanni; Minassi, Alberto
Graphical abstract: Highlights: The synthesis of a hybrid of colchicine and griseofulvin is proposed. The synthetic strategy is based on an oxidative cyclization reaction. Hypervalent iodine(III) reagents are used to create the spiro-dienone moiety. Abstract: Since the antimitotic agent colchicine (4 ) and the antifungal antibiotic griseofulvin (5 ) bind the same target (tubulin), we have explored the possibility of combining the potency of4 and the low-toxicity of5 into a hybrid [colchifulvin (6 )], where the aromatic A-ring of4 is bound to a dienone C-ring in a spiro fashion reminiscent of5 . To this purpose, the intramolecular oxidative cyclization of bibenzyl and stilbenoid precursors of spiro[4.5]decadienones was investigated, eventually taming the unexpected subtleties of the reaction. Disappointingly, rac -6 did not share the biological profile of the two inspiring lead structures.